TEKNOLOGI PENGOLAHAN AIR ASAM TAMBANG BATUBARA Ã¢â‚¬Å“Alternatif Pemilihan TeknologiÃ¢â‚¬Â - Said, Nusa Idaman (Jurnal Air Indonesia, 2014)
Acid Mine Drainage (AMD) treatment systems can be broadly categorised as either active or passive systems, which differ according to their ability to handle Acidity, flow rate and Acidity Load of the influent AMD. Most passive and active systems utilise aggregate carbonate to neutralise the pH and encourage precipitation of metals as hydroxides or sulphide minerals. In addition, passive treatment systems often use organic matter to provide alkalinity and create reducing conditions which favour the precipitation of metal sulphides.Active treatment systems can be engineered to accommodate essentially any acidity, flow rate and acidity load. Active treatment of AMD can be achieved using fixed plants or portable equipment for in-situ treatment. Passive treatment systems are almost invariably used for post closure treatment scenarios, and are best suited to AMD with low Acidity and low flow rates. The key factors in selection and design of active and passive AMD treatment systems are water chemistry including pH, metals, sulphate levels and redox state and flow rate of influent AMD, and the objectives of AMD treatment. Other important factors include capital and operating costs, availability of suitable treatment reagents or materials and sludge management issues. Keywords: Acid Mine Drainage, Active Treatment, Passive Treatment, Coal Mining.